Neutrophils Encompass a Regulatory Subset Suppressing T Cells in Apparently Healthy Cattle and Mice - Rambault, Marion; Doz-Deblauwe, Émilie; Le Vern, Yves; Carreras, Florence; Cunha, Patricia; Germon, Pierre; Rainard, Pascal; Winter, Nathalie; Remot, Aude (Frontiers in Immunology, 2021)
Neutrophils that reside in the bone marrow are switly recruited from circulating blood to fight infections. For a long time, these first line defenders were considered as microbe killers. However their role is far more complex as cross talk with T cells or dendritic cells have been described for human or mouse neutrophils. In cattle, these new roles are not documented yet. We identified a new subset of regulatory neutrophils that is present in the mouse bone marrow or circulate in cattle blood under steady state conditions. These regulatory neutrophils that display MHC-II on the surface are morphologically indistinguishable from classical MHC-IIneg neutrophils. However MHC-IIpos and MHC-IIneg neutrophils display distinct transcriptomic profiles. While MHC-IIneg and MHC-IIpos neutrophils display similar bacterial phagocytosis or killing activity, MHC-IIpos only are able to suppress T cell proliferation under contact-dependent mechanisms. Regulatory neutrophils are highly enriched in lymphoid organs as compared to their MHC-IIneg counterparts and in the mouse they express PDL-1, an immune checkpoint involved in T-cell blockade. Our results emphasize neutrophils as true partners of the adaptive immune response, including in domestic species. They open the way for discovery of new biomarkers and therapeutic interventions to better control cattle diseases.